Analysis of the Effectiveness of the Interest Rate Channel Monetary Policy Transmission Mechanism for Non-Performing Loans of Conventional Commercial Banks in Indonesia 2018 – 2022 - Yustika Arga Puspita; Karsinah Karsinah (Jurnal Indonesia Sosial Teknologi, 2024)
Monetary policy is a policy set by the central bank to influence the circulation of money in the economy, which is reflected in the development of the money supply, interest rates, credit, exchange rates, and various other economic and financial variables. This study aims to analyze the influence of the implementation of women's rights in the Manpower Law on the level of welfare of women workers in the industrial sector. In the context of gender inequality that still occurs, it is important to explore how existing regulations can improve women's living and working conditions. This study uses a quantitative method with a sample consisting of female workers in several industrial companies. Data was collected through surveys that assessed the understanding and implementation of women's rights in the workplace, as well as their impact on their well-being. Data analysis was carried out using statistical techniques to test the hypothesis proposed. The results of the study are expected to provide a clear picture of the effectiveness of existing policies and their contribution to improving the welfare of women workers. The findings are also expected to serve as a reference for policymakers and companies in formulating better strategies to support women's rights in the industrial sector.